Analysis of factors affecting the incidence of anemia in adolescent girls at Nawangsasi Health Center: A cross-sectional study - Puspitasari, Ema; Zaman, Chairil; Harokan, Ali; Suryani, Dewi (Lentera Perawat, 2025)
Background Anemia is one of the most common public health problems among adolescent girls, potentially leading to decreased concentration, impaired growth, and reduced immune function. The prevalence of anemia in this age group remains high, both globally and nationally. Objective This study aimed to analyze the factors influencing the incidence of anemia among adolescent girls in the working area of Nawangsasi Public Health Center, Musi Rawas District. Methods A quantitative study with a cross-sectional approach was conducted involving 72 adolescent girls selected using purposive sampling. Data were collected through interviews using a structured questionnaire and analyzed using chi-square tests and logistic regression. Results There were significant associations between nutritional status (p = 0.006), iron tablet consumption (p = 0.009), and dietary patterns (p = 0.019) with the incidence of anemia. The most dominant factor was dietary pattern (p = 0.026), with an odds ratio of 11.00 (95% CI = 1.33–90.61). Conclusion Improving dietary habits and increasing adherence to iron supplementation play a crucial role in anemia prevention among adolescent girls. Continuous nutritional education and behavioral monitoring through multisectoral collaboration are recommended to effectively reduce anemia prevalence in this population.